A Meta‐analysis of intradermal versus intramuscular influenza vaccines: Immunogenicity and Adverse Events. Issue 4 (13th September 2012) - Marra, Fawziah; Young, Flora; Richardson, Kathryn; Marra, Carlo A.
<x xml:space="preserve">Abstract</x> Please cite this paper as: Marra et al. (2012) A Meta‐analysis of intradermal versus intramuscular influenza vaccines: immunogenicity and adverse events. Influenza and Other Respiratory Viruses 7(4), 584–603. Objective To determine immunogenicity and safety of intradermal (ID) influenza vaccines compared with intramuscular (IM) administration and effect of dose and age. Design Meta‐anlysis. Setting Systematic review and meta‐analysis of randomized controlled trials on influenza vaccines. Sample Randomized, controlled trials comparing ID seasonal split‐virus influenza vaccines with 15 μg IM control in subjects 18 years of age or older and assessed antibody response at 21–28 days post‐vaccination were considered for inclusion. Results A total of 13 trials were included. The pooled immunogenicity outcomes did not differ significantly between the IM and ID vaccine groups for the H1N1 (ratio of GMTR: 0·92, 95% confidence interval 0·77–1·09; seroconversion: 0·94, 0·86–1·02; seroprotection: 0·97, 0·94–1·00) and B strains (GMTR: 0·93, 0·80–1·08; seroconversion: 0·91, 0·80–1·04; seroprotection: 0·97, 0·91–1·03). For the H3N2 strain, there was no significant difference in GMTR (0·97, 0·80–1·18); however, there was a lower pooled seroconversion (0·89, 0·80–0·99) and seroprotection rate (0·98, 0·96–0·99) for ID recipients. There was a statistically significant association between increasing doses of the ID vaccination with increasing immunogenicity response (P = 0·01). There were no differences in adverse event rates within 3 days post‐vaccination for ID versus IM. But for adverse events occurring 7 days post‐vaccination, ID vaccination was associated with a greater incidence of local events but not systemic events. Conclusions There was no significant difference in immunologic response when comparing ID with IM administration of the influenza vaccination in the overall population, but higher doses of ID vaccine in the older adult population produced a better response.